Providing a Dynamic Model for New Product Development in the Field of Financial Regulatory Technologies - Soroush Motamedi Fard ; Amir Bayat Tork; Jalal Haghighat Monfared (مطالعات مدیریت کسب و کار هوشمند, 2020)
In today's fast-paced and highly uncertain environment where customer needs, technology, employee needs, community status, monetary systems, geographic location and everything are changing, companies cannot always rely on the production and supply of their existing products. A new product development strategy is an important activity that helps companies stay alive and make continuous improvements. However, most organizations consider these factors static and disregard these dynamics. Since the relationship between the factors contributing to the success of new product development has many dynamics and feedbacks, the systems dynamics tool is a useful tool to analyze in this area. In this research, in order to identify and analyze the dynamics of the factors affecting the success of a new product development, based on the theoretical background and opinions of industry experts, key variables in the field of new product development have been identified and the causal relationships between these variables are outlined. Accordingly, the system simulated in Tejarat Bank from 1392 to 1404. The results of the simulation and review show that considering the considered policies optimizes the new product development of regulatory financial products in the aforementioned organization.